BARRIERS ASSOCIATED WITH HIV SELF-TESTING AMONG LIRA UNIVERSITY STUDENTS. A CROSS-SECTIONAL STUDY. - Ssemakula, Peter; Opollo , Marc Sam Opollo; Modi, Derick; Kayizzi, Julius (Student’s Journal of Health Research Africa, 2024)
Background HIV continues to be a significant public health concern, particularly among the young population in our communities, determining the barriers associated with HIV self-testing is very crucial for effective HIV prevention. Therefore, this study aimed to determine the barriers associated with HIV self-testing among the students of Lira University. Methodology This study employed a descriptive cross-sectional design, stratified simple random sampling was used, where faculties acted as strata, and then systematic sampling was used to obtain the participants from each year of study. Quantitative data was collected using self-administered questionnaires. Results According to the findings, 174 respondents participated in this study, 90(51.7%) were males while 84(48.3%) were female. The age category 20-25 had 145(81.6%) respondents while 31-40 had 25(14.4%) respondents, single respondents were 154(88.5%), Year one had 92(52.9%) respondents, and Year Two had 30(17.2%) respondents, Education Faculty had 59(33.9%) respondents, and the Faculty of Management Sciences were 11(6.3%) respondents. The barriers to the use of HIVST services included Lack of Knowledge 113(64.9%), Concerns about the accuracy138 (79.8%), and Lack of counseling and support services 114(65.5%). Participants with less knowledge were less likely to use HIV self-testing services compared to those who had ever heard about HIVST services cOR: 6.438, p<0.001 also those lacking counseling and support services were less likely to have ever used HIVST services compared to those who had ever attended counseling and support services aOR: 13.265 p<0.001. Conclusion The study found that the majority of the respondents were year-one single males from the faculty of education, and their less knowledge of self-testing hindered the use of HIVST services. Recommendation Education Programs should be carried out to disseminate information and knowledge about barriers to HIVST services among students.